PEMBELAJARAN KEWARGANEGARAAN (PKN) YANG KONTEKSTUAL DAN MENYENANGKAN BAGI SISWA SEKOLAH DASAR - Roni Agus Subagyo; Ahmad Muhibbin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explore and analyze contextual and fun learning approaches for Civic Education in elementary schools. The type of research is qualitative with literature review method. The learning strategies explored and analyzed include active and creative learning, media use, and learning models. The results showed that active and creative learning strategies, the use of technology-based and contextual interactive media, as well as project-based and cooperative learning models are effectively applied to create contextual and fun learning so as to increase students' understanding of Pancasila values. The implication is that teachers need to integrate contextual approaches creatively and utilize technology to support the Civics learning process. Further research needs to test the application of contextual and fun approaches in varied classroom conditions.